Conformationally Constrained Cyclic Peptides: Powerful Scaffolds for Asymmetric Catalysis1. (4th June 2014) - Zheng, Lifei; Marcozzi, Alessio; Gerasimov, Jennifer Y.; Herrmann, Andreas
Abstract Cyclic peptides containing a disulfide bridge were identified as a simple and versatile coordination sphere for asymmetric catalysis. Upon complexation with Cu2+ ions they catalyze Diels–Alder and Friedel–Crafts reactions with high enantioselectivities of up to 99 % ee and 86 % ee, respectively. Moreover, the peptides ligands were systematically optimized with the assistance of "Alanine Scanning". This biomolecular design could greatly expand the choice of peptide scaffolds for artificial metallopeptide catalysts.